Potential collusion and trust: Evidence from a field experiment in Vietnam - Torero, Máximo; Viceisza, Angelino (International Food Policy Research Institute, 2011)
We conduct framed trust games using contract dairy farmers in Vietnam as first movers to assess the impact of potential collusion on trust. Disaggregated analysis suggests that female farmers are more likely to trust overall, but are also more responsive to the addition of a third party and potential collusion. A third party induces them to trust at higher levels, but potential collusion between the trustee and the third party also induces them to trust at lower levels. Our findings corroborate well with existing studies on gender differences in decision making, which suggest that women's social preferences are more context-specific than men's.